International Business Economics / A European Perspective: Second Edition - Cook Mark; Piggott Judith (Longman, 1999)
This book provides students with an understanding of the international business environment both at a European and International level. Acknowledgements, Introduction, The Changing Nature of International Business, The Environment of International Business, International Trade, The Protection of Trade, Economic Integration, EU Policy Areas, Industrial Policy and Competition Policy, The Single European Market and Beyond, Multinational Corporations, Foreign Direct Investment, Foreign Exchange Markets, International Banking and Capital Markets, Central and Eastern Europe, Conclusion.